Network Topology Reconstruction Based on Power Line Communication - Xu Ma; Fang Yang; Jian Song; Jianqi Li; Weilin Liu (Dianxin kexue)
Power line communication（PLC）is playing a more and more important role in the smart grid（SG）. Apart from conveying information, to reconstruct the topology of the network is also very critical. By modeling the power line network as a tree structure and making full use of the property of“through the network”of PLC signal,it is possible to get the knowledge of the topology of network. The PLC channel model was considered and the topology of PLC network was reconstructed by taking advantage of the signal of the transmitter and receiver. The algorithm of matrix pencil and dynamic network reconstruction algorithm was performed. The simulation results show that both algorithms can reconstruct the network topology accurately with a high probability.